18-kDa translocator protein ligand 18F-FEMPA: Biodistribution and uptake into atherosclerotic plaques in mice - Hellberg S; Silvola JM; Kiugel M; Liljenbäck H; Savisto N; Li XG; Thiele A; Lehmann L; Heinrich T; Vollmer S; Hakovirta H; Laine VJ; et al. (My University, 2022)
18F-FEMPA shows rapid blood clearance and uptake in the mouse aorta. Uptake in atherosclerotic plaques correlated with the amount of macrophages, but did not exceed that in the normal vessel wall.